Interobserver Agreement in the Diagnosis of Inflammatory Bowel Disease-Associated Neoplasia in China in Comparison to Subspecialized American Gastrointestinal Pathologists. (23rd April 2018) - Wu, Xian-rui; Liu, Hua-shan; Shi, Xue-ying; Zhou, Wei-xun; Jiang, Zhi-nong; Huang, Yan; Karamchandani, Dipti M.; Goldblum, John R.; Xiao, Shu-yuan; Zhu, Hong-fa; Feely, Michael M.; Collinsworth, Amy L.; et al.
Abstract : Background . The aim of this study was to evaluate the interobserver variability in diagnosing inflammatory bowel disease (IBD)-associated neoplasia among practicing pathologists from China using telepathology, a practice of remote diagnostic consultation increasingly used nationally and internationally, and its comparison with the interpretation of subspecialized gastrointestinal (GI) pathologists from the United States (US). Methods . Eight GI pathologists from the US and 4 pathologists from China with an interest in GI pathology participated in this study. A total of 50 colonic biopsies from patients with a clinical history of IBD from 8 medical centers in China were included. All microscopic slides in each case were digitized using an Aperio system. One pathologist (XL) reviewed the digitized full-slide images, and selected areas of interest were captured at low, medium, and high magnifications at a resolution of 1712 × 1072 pixels and saved as tagged image file format (TIFF) files on read-only DVD. Each pathologist evaluated the images and selected the most appropriate diagnostic category for each case (negative, indefinite, low-grade dysplasia [LGD], high-grade dysplasia [HGD], and carcinoma). A Fleiss' kappa coefficient ( K ) analysis was performed to determine interobserver agreement and the agreement of each pathologist from China with the consensus diagnosis (defined as diagnostic agreement by at least 4 participating US GI pathologists). Results . There was substantial interobserver agreement among 4 pathologists from China on the interpretation of IBD-associated neoplasia (kappa value 0.68, 95% confidence interval: 0.56–0.78). A consensus diagnosis included negative (n = 22 ), LGD (n = 22 ), HGD (n = 3 ), carcinoma (n = 2 ), and indefinite for dysplasia (n = 1 ). Using consensus diagnoses as references, the agreement between each pathologist from China and the consensus diagnosis was substantial with kappa values ranging from 0.75 to 0.80. Conclusions . This study reveals substantial interobserver agreement for the interpretation of colonic neoplasia in IBD using digitized images among Chinese pathologists as well as between each Chinese pathologist and a consensus diagnosis generated by US GI pathologists.